The Paragenetic Stage of the Dongping Gold Deposit in the Northern Margin of the North China Platform - Chao, Yuhong; Yin, Jianzhao; Yin, Yuhan; Xiang, Shoupu; Shi, Hongyun; Wang, Jiapeng (European Journal of Applied Sciences, 2022)
The Dongping gold mine, located at the northern margin of the North China Platform, is one of the few large-scale gold deposits in China related to alkaline complex intrusions. In view of this, in-depth dissection of its causes is not only of geological theoretical significance, but also helps to find more similar gold resources under similar geological background, so as to benefit local people. To achieve the above goals, it is necessary to accurately grasp the paragenetic process of the deposit, that is, its paragenetic period and paragenetic stage. Through detailed field and laboratory research, the authors of this paper concluded that the formation of the Dongping gold deposit was the result of multi-stage paragenetic process. Specifically, the formation of the Dongping gold deposit has gone through the following four paragenetic stages, namely (from early to late): Milky white quartz (Q1)-potassium feldspar (K1)-coarse grained pyrite (cgPy) stage, Grey white quartz (Q2)-brick-red potassium feldspar (K2) stage, Potassium feldspar (K3)-quartz (Q3)-polymetallic sulfide stage, and Calcite-chert (Q4)-barite stage. Among them, the third stage, that is, the Potassium feldspar (K3)-quartz (Q3)-polymetallic sulfide stage, is the most important paragenetic stage, marking the climax of the gold mineralization of the deposit.